Antioxidant and Antiapoptotic Properties of n-Butanol Fraction the Acanthopanax senticosus Extracts in H2O2-RAW264.7 Cells and CCl4-Induced Liver Injury in Mice. (23rd February 2023) - Su, Jianqing; Fu, Xiang; Liu, Ruixue; Zhang, Xinyu; Xue, Jiaojiao; Li, Ying; Zhang, Rui; Li, Xiaoli; Wang, Xiaoya; Wang, Xueyan; Ding, Yi; Chu, Xiuling
Abstract : The Acanthopanax senticosus has been shown to have a wide range of pharmacological activities, which are associated with health benefits, such as antioxidant, anti-inflammatory, and antiapoptotic properties. A previous study has shown that the n-butanol fraction of A . senticosus extract had the strongest antioxidant effect in vitro. This study aimed to investigate the effects that the n-butanol fraction of A . senticosus extract could relieve oxidative stress damage through antioxidant and antiapoptotic in the H2 O2 -stimulated RAW264.7 macrophages and the CCl4 -induced liver injury. The result showed that the n-butanol fraction extract could relieve damage by increasing the intracellular antioxidant enzymes (SOD) level, decreasing intracellular ROS and MDA levels, and regulating antioxidant and antiapoptotic-related gene expression levels. The morphological observation of HE, TUNE, and immunohistochemistry staining of liver tissue verified that the n-butanol fraction extract is though anti-oxidative and antiapoptotic to alleviate cellular oxidative damage. The RT-PCR assay showed that the Keap1-Nrf2-ARE and the Bax/Bcl-2 signaling pathway were related to the molecular mechanism of action. The experimental results show that Acanthopanax senticosus extract has a good effect in treating liver injury and enhancing the antioxidant capacity of the body.